MENJADI GENERASI UNGGUL DAN BERKARAKTER UNTUK MENGGAPAI KESUKSESAN - Ngatipan Ngatipan (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The superior generation is a generation that has intelligence and good character within itself, always has a positive impact on oneself, others and creatures around their environment. Education that can give birth to a superior generation is education that can also strengthen the will so that everyone who knows moral goodness really wants to live according to the knowledge they have. The superior generation is the product or result of the habituation of character values ​​originating from spiritual intelligence. is the ability to "feel" one's diversity. Spiritual intelligence (SQ) is intelligence related to transcendent things, things that "overcome" time. It transcends the present and human experience. He is the most important part of humans and science (neuroanatomy and neurochemistry), proving that SQ is based on the human brain.